Three-dimensional simulation of microwave heating coal sample with varying parameters. (25th January 2016) - Hong, Yi-du; Lin, Bai-quan; Li, He; Dai, Hua-ming; Zhu, Chuan-jie; Yao, Hao
Highlights: The effect of frequency, power and sample position on temperature was discussed. The relation between microwave energy and power changes with heating temperature. There is one optimal frequency to achieve the maximum or minimum temperature. The effect of sample position on the temperature is also remarkable. Abstract: This paper aims to predict the heating behaviors of coal sample by COMSOL Multiphysics software based on the finite element method. The effects of microwave frequency, microwave power and sample position on temperature profiles and electric field distributions are examined. The effect of microwave frequency on temperature is obvious. The maximum and minimum temperatures of the coal sample change with frequency in different laws respectively. There is just one optimal heating frequency to achieve the maximum or minimum value of temperature. The effect of microwave power on temperature is found evidently, too. The lower power microwave-treatment requires more energy than microwave-treatment with a higher power when the heating temperature is greater than 200 °C. And there is an optimal temperature between 100 °C and 200 °C, which energy input is equal to each other under different power inputs. The effect of sample position on the temperature is also remarkable. The maximum and minimum temperatures of the coal sample change with position in different laws respectively. The results can serve as references for the study on heating coal sample by microwave heating system.